Spatiotemporal differences and influencing factors of the dietary structure index in Chinese urban residents - Tianyang Chen; Zheng Guo; Zheng Guo; Sophia Shuang Chen; Sophia Shuang Chen; Giri Raj Kattel; Giri Raj Kattel; Giri Raj Kattel; Shimou Yao (Frontiers in Sustainable Food Systems)
The diversity of urban residents’ dietary in China has increased with socioeconomic development. However, still there is a prominent problem of unbalanced and inadequate regional development of diet. Exploring the characteristics of the dietary structure of urban residents in China as expressed by Dietary Structure Index (DSI) holds greater significance for healthier China. This paper analyzes the spatiotemporal differentiation and influencing factors of the DSI of Chinese urban residents, and concludes that from 2015 to 2022, the average values of DSI of Chinese urban residents showed a significant upward trend. Specifically, the comprehensive DSI and animal-based DSI still have a significant gap with the scientifically recommended balanced dietary pattern, while the plant-based DSI is generally higher. There is a clear regional pattern in the spatial distribution of the DSI of urban residents in China, which generally shows a decreasing trend from northeast to southwest. The spatial agglomeration of the comprehensive DSI and the animal-based DSI are significantly higher than the plant-based DSI. In general, the DSI of Chinese urban residents is positively correlated with the level of consumption, urbanization, and education, while negatively correlated with the consumer price index. We propose promoting plant-based diets and reducing excessive meat consumption in high-DSI regions, while leveraging urban infrastructure to deliver nutrition education and providing subsidies for healthier food options in markets. In low-DSI regions, interventions should focus on incentivizing local production of vegetables and legumes through agricultural subsidies, expanding cold-chain logistics to enhance the distribution of perishable foods, and establishing community-based nutrition programs to improve residents’ food literacy, and argue that these are the potential measures to optimize the dietary structure of Chinese urban residents.